Implication of FIFA 2022 on Active Living and Environmental Changes: A Managerial Perspective - Nair, Girish K. (Journal of Sustainability and Environmental Management, 2022)
This study is focused on the environmental impact of hosting FIFA 2022 in Qatar on the well-being and the active living of the residents. The primary data was collected through the questionnaire which was validated and tested using confirmatory factor analysis. The second-generation statistical analysis using Structural Equation Modelling (SEM) was adopted which undertakes both regression and factor analysis simultaneously using Partial Least Square Method. The results have shown that there is a significant influence of environmental factors on material-based factors, community-based factors, emotion-based factors, and health-based factors. Further, the community-based factor had significant influence on mental health, emotion-based factor has significant influence on social health, and health-based factor had significant influence on spiritual health. The environmental factors had significant influence on mental, social, and spiritual health. Surprisingly, the environmental factors and material-based factors had no significant influence on physical health. The implications of the study are in the form of suggestions to the managers of tourism industry and the strategic planners of FIFA 2022 in Qatar. Application of scenario planning tools may be required to make an estimate of the material-based factors. Optimum number of events to be hosted in the country may have to be estimated such that it contributes to the betterment of the community-based factors.